Pathophysiological Changes and the Role of Notch-1 Activation After Decompression in a Compressive Spinal Cord Injury Rat Model - Cheng, Xing; Yu, Zhengran; Xu, Jinghui; Quan, Daping; Long, Houqing (Frontiers in Neuroscience, 2021)
Surgical decompression is the primary treatment for cervical spondylotic myelopathy (CSM) patients with compressive spinal cord injury (CSCI). However, the prognosis of patients with CSCI varies, and the pathophysiological changes following decompression remain poor. This study aimed to investigate the pathophysiological changes and the role of Notch-1 activation after decompression in a rat CSCI model. Surgical decompression was conducted at 1 week post-injury (wpi). DAPT was intraperitoneally injected to down-regulate Notch-1 expression. Basso, Beattie, and Bresnahan scores and an inclined plane test were used to evaluate the motor function recovery. Hematoxylin and eosin staining was performed to assess pathophysiological changes, while hypoxia-inducible factor 1 alpha, vascular endothelial growth factor (VEGF), von Willebrand factor (vWF), matrix metalloproteinase (MMP)-9, MMP-2, Notch-1, and Hes-1 expression in the spinal cord were examined by immunohistochemical analysis or quantitative PCR. The results show that early decompression can partially promote motor function recovery. Improvements in structural and cellular damage and hypoxic levels were also observed in the decompressed spinal cord. Moreover, decompression resulted in increased VEGF and vWF expression, but decreased MMP-9 and MMP-2 expression at 3 wpi. Expression levels of Notch-1 and its downstream gene Hes-1 were increased after decompression, and the inhibition of Notch-1 significantly reduced the decompression-induced motor function recovery. This exploratory study revealed preliminary pathophysiological changes in the compressed and decompressed rat spinal cord. Furthermore, we confirmed that early surgical decompression partially promotes motor function recovery may via activation of the Notch-1 signaling pathway after CSCI. These results could provide new insights for the development of drug therapy to enhance recovery following surgery.